Development and Validation of a Taxonomy for Specific Questions Based on Deficiencies in Logical Reasoning - Qiu, Li; Ikeda, Fumihito; Yamashita, Naoko (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop a taxonomy of specific questions based on deficiencies in three types of logical reasoning: inductive, deductive, and hypothetical reasoning. The study also seeks to validate the quality of this taxonomy. Methodology: This study is a developmental research project that utilized a “three-level model” combining deductive approaches with empirical data analysis to develop and validate a taxonomy of questions. A convenience sampling method was employed, whereby 57 questions were selected from 1,164 posed by graduate students at a university in Japan. The question data were categorized by two raters. Descriptive statistics and the kappa coefficient method was employed to verify the quality of the categorization. Main Findings: The taxonomy of specific questions comprised nine categories, with three categories assigned to each type of logical reasoning. The comprehensiveness assessment results showed that all questions were assigned to one category, with at least one question included in each category. The results for exclusivity and objectivity revealed high kappa coefficients, indicating a high degree of agreement between raters. However, there was some confusion among question categories within the same reasoning method during the categorization process. Novelty/Originality of this study: The development of a taxonomy of specific questions based on logical reasoning deficiencies. This framework facilitates the design of strategies that enable learners to generate specific questions. The proposed method of assigning questions enables an objective assessment of learners’ proficiency in formulating specific questions and is expected to more effectively guide the support process.